Investigation of auditory health in individuals exposed to elevated hydrostatic pressure - Dieieva, Yuliia; Bondarenko, Yaroslava (ScienceRise: Medical Science, 2024)
As diving depth increases, various environmental factors influence the human body, potentially triggering a range of physiological and psychological responses. One of the most significant factors is hydrostatic pressure. To ensure safe diving, tables and additional devices are used to pre-plan the route and create a dive profile that helps prevent unpleasant and hazardous complications. Among pathological conditions that may arise during or after diving, ear damage is one of the most common, occurring in 40–63 % of cases, according to various authors. The aim of the study: This study aims to assess the condition of both the sound-conducting and sound-perceiving components of the auditory system in divers. Materials and methods: Between 2019 and 2023, the Department of Otorhinolaryngology at Bogomolets National Medical University conducted examinations and collected data from 59 individuals engaged in scuba diving with specialized equipment. The inclusion criteria were ages 18 to 55 and professional certification. Initial screening involved medical history collection and ENT examination. The following audiological assessments were conducted: pure-tone audiometry and impedance audiometry. Additional parameters such as total number of dives, maximum dive depth, and time since the last dive were also recorded. Results and discussion: Pure-tone audiometry results showed that median hearing thresholds in Group 1 were around 10 dB, whereas in Group 2, they were approximately 5 dB. Moreover, Group 1 exhibited significantly higher bone conduction thresholds across all tested frequencies. Conclusions: A strong positive correlation was established between anamnestic data (number of dives, maximum dive depth, and diving experience) and elevated bone conduction thresholds. This indicates that prolonged exposure to hydrostatic pressure and other diving-related factors (e.g., pressure changes, acoustic effects, potential barotrauma) may contribute to progressive hearing impairment. The strongest correlation between diving experience and perceptual sensitivity thresholds was observed, suggesting a cumulative effect on the auditory system. These findings emphasize the importance of regular auditory health monitoring among both professional and recreational divers and highlight the need to develop preventive measures to mitigate the adverse effects of increased hydrostatic pressure on the auditory system